Effect of Red Rot Pathogen (Colletotrichum falcatum) on the Nutritional Contents of Sugarcane in the Savannah Ecological Zone of Nigeria - B.G, Zakari,; Paulinus F.O.,; Chimbekujwo, I.B,; Basiri, B, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Sugarcane production in Nigeria faces significant challenges, with red rot disease caused by Colletotrichum falcatum being a major concern. This study aimed to assess the effect of red rot pathogen (Colletotrichum falcatum) on the nutritional contents of sugarcane in the Savannah Ecological Zone of Nigeria. The fungal pathogen was successfully isolated and identified from diseased sugarcane plants, and its pathogenicity was confirmed through induced red rot symptoms on sugarcane plants. All experiments were conducted using standard procedures and data were analyzed using Analysis of Variance (ANOVA) at 5% probability level of significance. Results of the proximate composition analysis highlighted differences in nutritional content between uninfected and infected sugarcane, with infected samples exhibiting higher moisture of 15.85%, ash, 6.36% and fiber content 1.56%, against 6.68%, 6.30% and 1.24% of uninfected samples. While the uninfected samples having higher protein 1.72% and carbohydrate content 84.06% as against 1.11% and 79.59% of infected samples. Although proximate analysis results showed differences in the nutritional contents of the infected and uninfected sugarcanes, analysis of variance show significant difference between infected and uninfected samples in terms of carbohydrates and proteins contents, however, no significant difference existed between the two samples in terms of ash and fibre contents. Overall, it is clear from the result that the fungus not only cause red rot on sugarcane plants but also reduces the carbohydrates and proteins contains of sugarcane and by extension quality of sugar as well which might have a remarkable effect on the value of the sugar. It is therefore recommended timely spraying of the cane with fungicides to reduce the damaging activities of the pathogen and contamination with mycotoxins and other related fungal metabolites that might be harzadous to human health.